Enhancing the sensitivity of nanoplasmonic thin films for ethanol vapor detection - Rodrigues, Marco S. (2020)
Nanoplasmonic thin films, composed of noble metal nanoparticles (gold) embedded in an oxide matrix, have been a subject of considerable interest for Localized Surface Plasmon Resonance (LSPR) sensing. Ethanol is one of the promising materials for fuel cells, and there is an urgent need of a new generation of safe optical sensors for its detection. In this work, we propose the development of sensitive plasmonic platforms to detect molecular analytes (ethanol) through changes of the LSPR band. The thin films were deposited by sputtering followed by a heat treatment to promote the growth of the gold nanoparticles. To enhance the sensitivity of the thin films and the signal-to-noise ratio (SNR) of the transmittance–LSPR sensing system, physical plasma etching was used, resulting in a six-fold increase of the exposed gold nanoparticle area. The transmittance signal at the LSPR peak position increased nine-fold after plasma treatment, and the quality of the signal increased six times (SNR up to 16.5). The optimized thin films seem to be promising candidates to be used for ethanol vapor detection. This conclusion is based not only on the current sensitivity response but also on its enhancement resulting from the optimization routines of thin films’ architectures, which are still under investigation.